Education 3590. Moral education. No. 22. Interview with Rev. Fr. J. Forliti. - Magsino, Romulo F. (Teacher)
Dr. Romulo Magsino interviews Rev. Fr. J. Forliti on the role of the school and family in moral education. An ETV production.